Deposition Model of Point Bar Sand of Ancient Bengawan Solo as Regional Groundwater Reservoir in Ngloram - Cepu, Central Java Blora - Yohanes, Moch. (Forum Geografi, 1999)
While the geological study of sedimentary sand point bar of river is scientifically attractive, economically sedimentary sand is a material for the building. The sedimentary sand point frequency contains metal and nonmetal prescripitation that has a highly economical value. It also functions as a reservoir of good rock water, because it hasÂ  good porosity and permeability. The sedimentary sand point bar of Bengawan Solo that has been for 600.000 years ago in Ngloram-epu, has the thickness approximately around 5 â 25 m, grown horisontally around 5 â 7 km, and locatedÂ  > 50 km2 which covers Ngloram-Wado-Kedungtuban. The sandy rock functioned as a good groundwater reservoir rock. The sand point bar in Bengawan Solo is precipitated on the stairs of Bengawan Solo that is situated on the clay rock having tongue formation. The water of reservoir point bar is expected to fulfill the needs of 100.000 inhabitants in Cepu and the cities around.